Validation of the Spanish Version of the VERITAS-PRN Scale to Assess Adherence to on Demand Regimens in Patients with Hemophilia - Torres-Ortuño A (Patient Preference and Adherence, 2021)
Ana Torres-Ortuño,1 Rubén Cuesta-Barriuso,2,3 Joaquín Nieto-Munuera,1 Álvaro Castiello-Munuera,1 José Antonio López-Pina4 1Department of Psychiatry and Social Psychology, University of Murcia, Murcia, Spain; 2Department of Physiotherapy, University of Murcia, Murcia, Spain; 3Royal Foundation Victoria Eugenia, Madrid, Spain; 4Department of Basic Psychology and Methodology, University of Murcia, Murcia, SpainCorrespondence: Rubén Cuesta-BarriusoDepartment of Physiotherapy, University of Murcia, Murcia, SpainTel +34 868887286Email ruben.cuestab@gmail.comIntroduction: The episodic or on-demand administration of clotting factor concentrates in hemophilia patients in the event of hemorrhage is employed to restore hemostasis. Adherence to on-demand treatments needs to be assessed in order to improve patient management, avoiding adverse effects and serious clinical complications.Aim: To validate the Spanish version of the treatment adherence scale in patients with hemophilia, namely, Validated Hemophilia Regimen Treatment Adherence Scale-PRN (VERITAS-PRN).Methods: Eighty-five patients were recruited in three hemophilia patient associations in Spain. The VERITAS-PRN scale was adapted through a back-translation process from English to Spanish. A native Spanish bilingual translator translated the scale from English to Spanish, and subsequently another native English bilingual translator translated the scale from Spanish to English. The scale was applied twice (two months apart) to assess test–retest reliability.Results: Internal consistency reliability was slightly lower in the VERITAS-PRN in Spanish (0.80) versus the English version (0.85). There were no differences (p > 0.05) between the means of the dimensions or in the total scores between the sample of patients in Spain and the USA. The test–retest reliability coefficient of the scores on the total scale was 0.80 [CI, 0.74– 0.86]. The test–retest reliability coefficient was greater than 0.90 in all subscales.Conclusion: The Spanish version of VERITAS-PRN has high consistency and empirical validity. This scale is useful for assessing the degree of adherence to treatment in adult patients with hemophilia following episodic infusion treatment.Keywords: hemophilia, adherence, validity, reliability, on-demand treatment, VERITAS-PRN